Ruptured Splenic Artery Aneurysms and the Use of an Adapted Fast Protocol in Reproductive Age Women with Hemodynamic Collapse: Case Series. (9th March 2014) - Jackson, Hope T.; Diaconu, Silviu C.; Maluso, Patrick J.; Abell, Bruce; Lee, Juliet
Abstract : Nontraumatic symptomatic hypotension in all patients requires prompt diagnosis and appropriate treatment for optimum outcome. The female population specifically has an expanded differential diagnosis that should be considered when these patients present with hemodynamic collapse. While the most common causes of hypotension in pregnant patients are dehydration, ruptured ectopic pregnancy, and placental and uterine abnormalities, less common nonobstetrical etiologies such as hepatic rupture and ruptured abdominal and visceral artery aneurysms should also be considered. Splenic artery aneurysms are associated with high rates of mortality and in cases of pregnancy, maternal and fetal mortality. These high rates can be attributed to the asymptomatic nature of the aneurysm, rapid deterioration after rupture, and frequent misdiagnosis. In patients with hemodynamic collapse, the role of traditional imaging is limited mainly due to the critical condition of the patient. Bedside ultrasound has emerged as a diagnostic imaging resource in patients with undifferentiated hypotension and in patients with traumatic injuries. However, its use has not been studied specifically in the female population. We present two patients with ruptured splenic artery aneurysms, discuss the role of bedside ultrasound in their management, and introduce a new ultrasound protocol for use in reproductive age female patients with hemodynamic collapse.